Abordagem histórica sobre o café no estado de São Paulo e suas relações sociais - Gazzola , Vivian Benfatti (Universidade Federal de São Carlos, 2025)
This paper provides a historical approach to the coffee commodity in the state of São Paulo through a narrative review. Brazil is the world's largest coffee producer and exporter, and the Port of Santos, in São Paulo, has contributed significantly to consolidating this position over the decades. Cultivated primarily in the Coffea arabica and Coffea canephora species, coffee shaped social dynamics in the state of São Paulo, which for many years was the largest coffee producer in Brazil. Production in the state followed national patterns: for large-scale export, a structure that led to political disputes, the slavery era, as well as the racist legacy of this practice, the elitism of "Café society," the popularization of the everyday black coffee, and the return of gourmet coffee with "postmodern coffee." After the decline of coffee in the state, São Paulo became the third largest coffee producer in Brazil, but has the opportunity to integrate into current trends with the growing appreciation of differentiated and certified coffees, in line with contemporary demands for sustainability and innovation in the global market.
Historical approach to coffee in the state of São Paulo and its social relations
Keywords: Café no estado de São Paulo; História paulista; Políticas agrícolas; Ondas do café; Coffee in the state of São Paulo; São Paulo's history; Agricultural policies; Coffee trends.; CIENCIAS AGRARIAS